Non-vitamin K antagonist oral anticoagulant discontinuation in non-valvular atrial fibrillation patients (ASPECT-NOAC). (14th October 2021) - Asilturk, E; Tulmac, M; Badak, Ö; Onal, T; Aras, D; Aciksari, G; Alper, A.T; Celik, A; Katicibasi, T; Ozdogan, O; ,
Abstract: Background and aim: Data on NOAC discontinuation patterns in Turkey are lacking. We conducted a subgroup analysis in ASPECT-NOAC study to determine anticoagulant discontinuation pattern in AF patients with recently initiated NOAC therapy. Methods: ASPECT-NOAC was a national, multicenter, 12-month observational study conducted in 34 outpatient cardiology clinics of state, university, private, and research hospitals covering all geographic regions of Turkey. Adult AF patients who were under NOAC therapy for less than four months were enrolled. Patients who discontinued using their NOACs were recorded at the end of 12 months. A comparative analysis of patients with discontinuation of medication was conducted. Results: This study included 991 non-valvular AF patients. NOAC continuation data were available for 854 patients. During study follow-up, 74 patients (8.7%) discontinued their NOAC medication. Mean age of these patients was 67.1±11.3 years old and 38 patients (51.4%) were female. Most commonly seen comorbidities were hypertension (66.2%) and coronary heart disease (39.2%). 29 patients (39.2%) had permanent (chronic) AF, followed by 26 patients (35.1%) with paroxysmal AF. Major reason for NOAC discontinuation was stated as physician request (n=46, 62%). Following reasons were patient request (n=17, 23%), other (n=9, 12%), and bleeding (n=2, 3%). Patients with NOAC discontinuation had a shorter duration of AF (21.7±41.7 vs 26.2±53.7 months, p=0.017). There was no significant difference of educational levels between medication discontinuation subgroups (p=0.637). Other baseline characteristics and patient disease and treatment awareness levels were similar with the patients who continued their medication. Of 74 patients, two patients died during the study because of cardiac failure. Conclusion: NOAC continuity rate over 12 months was found to be high. NOAC discontinuation rate were higher in the patients with shorter duration of AF. Further studies with long-term follow-up detailing discontinuation reasons are warranted. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This study was funded by Pfizer.